Comparison of the ADNEX and ROMA risk prediction models for the diagnosis of ovarian cancer: a multicentre external validation in patients who underwent surgery - Landolfo, Chiara; Ceusters, Jolien; Valentin, Lil; Froyman, Wouter; Van Gorp, Toon; Heremans, Ruben; Baert, Thaïs; Wouters, Roxanne; Vankerckhoven, Ann; Van Rompuy, Anne-Sophie; Billen, Jaak; Moro, Francesca; et al. (British journal of cancer, 2024)
BACKGROUND: Several diagnostic prediction models to help clinicians discriminate between benign and malignant adnexal masses are available. This study is a head-to-head comparison of the performance of the Assessment of Different NEoplasias in the adneXa (ADNEX) model with that of the Risk of Ovarian Malignancy Algorithm (ROMA). METHODS: This is a retrospective study based on prospectively included consecutive women with an adnexal tumour scheduled for surgery at five oncology centres and one non-oncology centre in four countries between 2015 and 2019. The reference standard was histology. Model performance for ADNEX and ROMA was evaluated regarding discrimination, calibration, and clinical utility. RESULTS: The primary analysis included 894 patients, of whom 434 (49%) had a malignant tumour. The area under the receiver operating characteristic curve (AUC) was 0.92 (95% CI 0.88-0.95) for ADNEX with CA125, 0.90 (0.84-0.94) for ADNEX without CA125, and 0.85 (0.80-0.89) for ROMA. ROMA, and to a lesser extent ADNEX, underestimated the risk of malignancy. Clinical utility was highest for ADNEX. ROMA had no clinical utility at decision thresholds <27%. CONCLUSIONS: ADNEX had better ability to discriminate between benign and malignant adnexal tumours and higher clinical utility than ROMA. CLINICAL TRIAL REGISTRATION: clinicaltrials.gov NCT01698632 and NCT02847832.
Keywords: algoritmy; nádory vaječníků; retrospektivní studie; lidé; nemoci děložních adnex; senzitivita a specificita; Female; Adnexal Diseases; Sensitivity and Specificity; CA-125 Antigen; Ultrasonography; antigen CA-125; Retrospective Studies; Ovarian Neoplasms; ultrasonografie; Algorithms; ženské pohlaví; Humans